Limit Experiences A Study of Twentieth-Century Forms of Representation - Leociak, Jacek (Eastern European Culture, Politics and Societies, 2019)
In his work Limit Experiences, Jacek Leociak addresses questions that are fundamental to the twentieth-century experience: How can we represent such traumatic events as the Holocaust? Was Lyotard correct when he claimed that reality had succumbed to the gas chambers? How can we describe the «indescribable»? Moving seamlessly through such topics as the destruction of the Warsaw Ghetto, the carpet bombing of Dresden, and Jews left for dead in the Nazi execution pits who miraculously «exited the grave» alive, Professor Leociak succeeds in offering readers a profound representation of twentieth-century limit experiences by embedding them in a broad array of sources and building around them a rich historical context.